Los microcréditos de los socios del Banquito Comunitario Mazorca de Oro y su impacto socio económico de la Parroquia de San Pedro de Guayabal, Cantón Chillanes Provincia Bolívar en el periodo 2016-2017. - Garofalo Verdezoto, Ninfa Estefanía (2018)
The investigative work carried out was carried out as a purpose, to analyze the impact of the microcredit obtained by the members of the Community bank “Mazorca de Oro” within the San Pedro de Guayabal Parish, for which it was necessary to gather information inside the bank on : the members, classification and number of credits granted during January 1, 2016 and March 31, 2017; for the determination of the impact of microcredit, criteria such as: job creation, credit satisfaction, credit consumption, increase of income by partners, improvements in living conditions, creation of enterprises, how much microcredits contribute; whether or not they contributed to socio-economic development. After the analysis of the results obtained in the survey, it is obtained that: the partners perceive positively the microcredits, this is due to the fact that thanks to the assumed debt they have been able to have an acceptable personal, familiar, economic and social development since, thanks to the money granted have become small microentrepreneurs. Key words: microcredit, development, socioeconomic, community bank.